Corporate social responsibility benefits and company image: An embedded mixed-method inquiry - Widayat Widayat; Afrizal Indra Syahputra; Novita Ratna Satiti (Jurnal Kajian Manajemen Bisnis, 2022)
This study aims to examine public perceptions of the social, economic, and environmental benefits of Corporate Social Responsibility (CSR) programs on corporate image. Data were taken from a sample of visitors to CSR objects using questionnaires and interviews, at famous landmarks created by the CSR practices of tobacco companies. Accidental sampling was used to represent respondents at the research site. Partial Least Square-Structural Equation Modeling playing SmartPLS, was used for the proposed model. Data from interviews was analyzed with Nvivo. This study found that people have a positive view of the social and environmental benefits of CSR, but most have a bad opinion about the economic benefits. The finding shows that the public's perception of environmental, economic, and social benefits has a significant impact on the company's image. CSR practices can support the community's economy, soc,iety and the environment by offering a comfortable, calm, and pollution-free atmosphere. Besides that, it is a comfortable place for business relations, sports, and gathering with family